Midazolam Activates the Intrinsic Pathway of Apoptosis Independent of Benzodiazepine and Death Receptor Signaling. Issue 4 (1st June 2011) - Stevens, Markus F.; Werdehausen, Robert; Gaza, Nina; Hermanns, Henning; Kremer, David; Bauer, Inge; Küry, Patrick; Hollmann, Markus W.; Braun, Sebastian
Abstract : Background and Objectives: Midazolam has neurotoxic properties when administered neuraxially in vivo. Furthermore, midazolam induces neurodegeneration in neonatal animal models in combination with other general anesthetics. Therefore, this study focuses on the mechanism of neurotoxicity by midazolam in neuronal and nonneuronal cells. The study aims to evaluate the apoptotic pathway and to investigate the protective effects of the benzodiazepine antagonist flumazenil and the caspase inhibitor N -(2-quinolyl)valyl-aspartyl-(2, 6-difluorophenoxy)-methylketone. Methods: The apoptosis-inducing effect of preservative-free midazolam on human lymphoma and neuroblastoma cell lines was evaluated using flow cytometric analysis of early apoptotic stages (annexin V/7AAD) and caspase 3 activation. B-cell lymphoma (Bcl2) protein overexpressing and caspase 9-deficient lymphoma cells were used to determine the role of the mitochondrial (intrinsic) pathway. Caspase 8-deficient and Fas-associated protein with death domain (FADD)-deficient cells were used to evaluate the death receptor (extrinsic) pathway. The protective effects of flumazenil and the caspase inhibitor N -(2-quinolyl)valyl-aspartyl-(2, 6-difluorophenoxy)-methylketone were investigated in neuroblastoma cells and primary rat neurons using metabolic activity assays (2, 3-bis(2-methoxy-4-nitro-5-sulfophenyl)-2 H -tetrazolium-5-carboxanilide) and immunofluorescence microscopy. Results: Midazolam induced apoptosis in all investigated cell types in a concentration-dependent manner, indicated by flow cytometry. Bcl2-overexpression and caspase 9 deficiency protected against toxicity, whereas caspase 8 or FADD deficiency had no effect. Pancaspase inhibition had a strong protective effect, whereas flumazenil did not inhibit midazolam-induced apoptosis. Conclusions: Midazolam induces apoptosis via activation of the mitochondrial pathway in a concentration-dependent manner. The mechanism of midazolam toxicity switches from caspase-dependent apoptosis to necrosis with increasing concentrations. The induction of apoptosis and necrosis by midazolam is presumably unrelated to GABAA receptor pathway signaling.